2020
DOI: 10.1056/nejmoa1907423
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Erythropoietin for Neuroprotection in Preterm Infants

Abstract: BACKGROUND-High-dose erythropoietin has been shown to have a neuroprotective effect in preclinical models of neonatal brain injury, and phase 2 trials have suggested possible efficacy; however, the benefits and safety of this therapy in extremely preterm infants have not been established. METHODS-In this multicenter, randomized, double-blind trial of high-dose erythropoietin, we assigned 941 infants who were born at 24 weeks 0 days to 27 weeks 6 days of gestation to receive erythropoietin or placebo within 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
260
2
8

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(280 citation statements)
references
References 41 publications
10
260
2
8
Order By: Relevance
“…For extremely preterm infants born at 24 to 27 weeks-of-gestation, Juul et al 2020 [147] published a Phase III Preterm EPO Neuroprotection (PENUT) clinical trial [NCT01378273] involving 936 subjects. It aimed to evaluate the effect of treatment with EPO on the combined effect of death or severe neurodevelopmental impairment at 24 months-of-age.…”
Section: Effects Of Epo In Clinical Trials For Preterm Infantsmentioning
confidence: 99%
“…For extremely preterm infants born at 24 to 27 weeks-of-gestation, Juul et al 2020 [147] published a Phase III Preterm EPO Neuroprotection (PENUT) clinical trial [NCT01378273] involving 936 subjects. It aimed to evaluate the effect of treatment with EPO on the combined effect of death or severe neurodevelopmental impairment at 24 months-of-age.…”
Section: Effects Of Epo In Clinical Trials For Preterm Infantsmentioning
confidence: 99%
“…On this background a recent multicenter (19 sites, 30 hospitals), randomized, double-blind trial of EPO was undertaken in 741 infants (24 to 27 6/7 weeks' 150 J.J. Volpe / Erythropoertin for premature brain gestation) [PENUT trial], i.e., preterm EPO Neuroprotection] [11]. Infants were administered EPO or placebo within 24 hours of birth and continued through 32 weeks' gestational age.…”
Section: Penut Trialmentioning
confidence: 99%
“…Thus, no differences between the EPO and placebo groups were observed at 22 to 26 months of age in the primary outcome of death or severe neurological impairment (26% vs. 26%), or in the key secondary outcome of death or moderate to severe neurodevelopmental impairment (48% vs. 47%). A limitation of the study, explicitly acknowledged by the investigators [11], is that cognitive testing at two years of age is not so reliable as testing at later ages [13]. Thus, a metaanalysis of 24 studies in which early assessments (by Bayley Scales of Infant Development-III or Griffiths Scales of Mental Development) performed at 1 1/2 to 3 years of age were compared with later cognitive tests carried out at school age showed that the pooled sensitivity of early assessments for identifying school-age cognitive deficits was only 55%.…”
Section: Penut Trialmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, high-dose EPO administration prompts newly differentiating neurons in the adult mouse brain [2]. Instead, it was recently showed that high-dose EPO treatment administered to extremely preterm infants from 24 hours after birth through 32 weeks of postmenstrual age did not result in a lower risk of severe neurodevelopmental impairment or death at 2 years of age [3]. Nevertheless, the primary cause of this discrepant phenomenon is still puzzling.…”
Section: Introductionmentioning
confidence: 99%